EVALUASI CITRA WORLDVIEW-2 UNTUK PENDUGAAN KEDALAMAN PERAIRAN DANGKAL PULAU KELAPA-HARAPAN MENGGUNAKAN ALGORITMA RASIO BAND - Tarlan Subarno; V P Siregar; S B Agus (Geoplanning: Journal of Geomatics and Planning, 2015)
Remote sensing technology is so advanced that recently produced satellite sensors with the capability to provide imagery options with very high spatial resolutions. One of the options is WorldView-2 that has 1.84 meter of spatial resolution. Besides, WorldView-2 also has at least five bands on visible rays. The capability of remote sensing for underwater detection through specific depths and the availability of its bands on visible rays give more appropriate options to apply logarithm bands ratio on shallow water depth estimation. This research is aimed at analyzing the capability of WorldView-2 imagery to estimate shallow water depth of Kelapa-Harapan islands by using bands ratio algorithm. There were six bands combination used in applying band 1 through band 4 of WorldView-2 imagery. The results have shown that the best combination of bands to estimate the shallow water depth in the study area is the ratio between band 1 and band 3 with the R2 value of 0.067 and the average bias of 0.66 m. The ratio between band 1 and band 4 gave the value of R2 as big as 0.55 of its regression to the field depth samples. Meanwhile, the other four bands combination ratios have shown very low correlations to the water depth in the field. © 2015 GJGP UNDIP. All rights reserved.